Best practices among 3rd third party logistics (3PL) firms towards logistics performance improvement in Malaysia - Mohamad Makmor, Mohamad Fared; Abdullah, Mokhtar; Saad, Mazni (Universiti Tunku Abdul Rahman (UTAR), 2018)
Studies on best practices among the Third3rd Party Logistics (3PL) firms towards logistics performance improvement has been conducted extensively nowadays due to the rising rivalry and the needs for survival in the business, especially for small players. Exploring the best practices structure as well as confirming its significance on firms’ overall performance has been validated by the concrete evidence of research literature and reports. The purpose of this paper is to study the breadth of best practices as found in the literature, with emphasizing on the effort to build a theoretical framework that further discover the adoption of best practices towards logistics performance improvement by 3PL firms in Malaysia. This paper discusses two independent theoretical areas, i.e. best practices and performance improvement in relation to the Malaysian’s logistics business operations. Exploring this theoretical areas suggest a research gap in which best practices are abstracted as a method that can be used to provide a confirmatory test of its theoretical support to a body of knowledge in the ground of logistics studies.